KARAKTERISTIK GLULAM BAMBU BETUNG (Dendrocalamus asper) MENGGUNAKAN PEREKAT STYROFOAM BERDASARKAN JUMLAH LAPISAN DAN POLA PENYUSUNAN - Anissa Mayliana Hidayah; Evi Sribudiani; Sonia Somadona (JURNAL ILMU-ILMU KEHUTANAN, 2022)
Bamboo is one of the non-timber natural forest products that has the potential to be used as raw material for wood substitutes because bamboo has many advantages. If for wood with high durability, it takes time from planting seedlings to be ready for harvest is 30-40 years and even then after cutting down the seeds must be planted again, but bamboo takes up to 4-5 years to be ready to be harvested. The problem that arises is that bamboo has a limited dimension so that it requires lamination technology that can shape bamboo into a dimensioned material according to construction needs. Lamination technology is an alternative way of processing bamboo that is relevant to achieving the expected goals. Lamination can make the strength of betung bamboo far higher than solid wood blocks. Tests carried out by physical and mechanical tests of betung bamboo lamination using JAS 234: 2003. Testing the physical properties of the betung bamboo includes a wood density test for moisture content testing, and thickness swelling. The mechanical properties of the betung bamboo include the modulus of repture and modulus of elasticity tests. The lamination test has variations in the number of layers A1 (3 layers), A2 (5 layers), and A3 (7 layers) with 3 replications each. betung bamboo density obtained an average of 0.316 gr/cm3 to 0.453 gr/cm3, the average moisture content of betung bamboo was 11.386% to 12.444%, and the average thickness swelling test was 0.240% to 0.293%. Modulus of repture test is 210,160 kg/cm2 to 925,963 kg/cm2, and the modulus of elasticity test shows an average of 0.916 kg/cm2 to 925,963 kg/cm2. The physical properties of the betung bamboo (Dendrocalamus asper) meet the JAS 234: 2003 standard is the moisture content, for the density and thickness swelling bamboo betung lamination is not required in the JAS 234: 2003 standard. The mechanical properties of betung bamboo laminate for MOE values are equivalent to wood strength classes II-IV and MOR are equivalent to wood strength classes V